Exploiting the non-medical value of waste expired aminophylline for lithium ion battery anode. Issue 1 (28th August 2018) - Dai, Zhipeng; Hou, Hongying; Liu, Xianxi; Yao, Yuan; Yu, Chengyi; Li, Dongdong
Abstract : Expired medicines in the environment may cause the pollution and resource waste if they are not reasonably recycled. Therefore, it is very instructive to exploit the non-medical values of expired medicines. Herein, such an attempt to recycle expired aminophylline was made as the anode active material of lithium ion batteries (LIBs) for the first time. The microstructure and chemical element component of the expired aminophylline were confirmed by using the methods of scanning electron microscopy, energy-dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. Furthermore, the feasibility of using an expired-aminophylline-based anode in LIBs was evaluated by galvanostatic charge/discharge and cyclic voltammetry. To be satisfactory, the reversible specific discharge capacities of expired-aminophylline-based anode were maintained at 268·8 mAh/g at 50 mA/g for 200 cycles and 140 mAh/g even at 500 mA/g for 1000 cycles. In addition, after coupling with a commercial lithium cobalt (III) oxide (LiCoO2 ) cathode, the resultant full cell also delivered 130 mAh/g at the 100th cycle at 100 mA/g. These satisfactory results may not only pave a way for the reasonable exploitation of the non-medical values of expired medicines but also offer good inspiration and strategy to develop sustainable energy and circular economy.